Electrodermal Activity Monitoring for Stroke Patients Stress States, Еmotional Disturbances, Rehabilitation Measures Effectiveness Specification: a Pilot Study - Anna A. Kuzyukova; Andrey P. Rachin; Vasiliy A. Kolyshenkov (Вестник восстановительной медицины, 2022)
INTRODUCTION. The level of stress experienced by stroke patients (caused by anxiety-depressive disorders, pain and motor deficiency) is still difficult to assess adequately clinically and with the help of existing diagnostic questionnaires, whereas their presence in a state of pronounced discomfort significantly affects the overall functioning and effectiveness of rehabilitation measures. In connection with the above, of interest are the methods aimed at objectification of stress level, such as determination of sympathetic activation byregistration of cutaneous conductivity, which, according to the literature, can be a reliable marker of affective pathology and chronic pain. AIM. To assess the possibility of using the NeonFSC stress monitoring system, RU No. RZN 2021/16179 dated December 29, 2021 for diagnostics by recording the skin conduction of stress, pain sensations and emotional pathology in stroke patients, and determining the effectiveness of the treatment and rehabilitation measures taken to correct the above disorders. MATERIAL AND METHODS. Thirty-five stroke patients were examined clinically and anamnesthetically, clinico-neurologically, clinicopsychopathologically,using diagnostic scales and recording electrodermal activity. RESULT AND DISCUSSION. The NeonFSC system determines the level of sympathetic activation in stroke patients, correlated with clinical parameters (neurological deficit, severity of pain, anxiety and depression) and helps to assess the dynamics of discomfort experienced by the patient as a result of rehabilitation measures. The use of electrodermal activity monitoring in a comprehensive examination of patients increased the diagnosis of emotional pathology and pain by 30%, objectified the presence of distress or its absence. CONCLUSION. The NeonFSC system is promising for use in comprehensive diagnosis and assessment of the dynamics of anxietydepressive disorders, pain, and other distress-inducing conditions, as well as to determine the adequacy of physical activities used in rehabilitation for various diseases.